Patient perceptions of clinical care in complementary medicine: A systematic review of the consultation experience. Issue 2 (February 2017) - Foley, Hope; Steel, Amie
Highlights: The first review of patients' clinical experiences in complementary medicine (CM). CM patients experience empathy, empowerment & patient-centred care in consultation. CM may be a valuable resource for meeting patients' psychosocial health needs. Abstract: Objective: This review aims to describe the prevalence of empathy, empowerment and patient-centred clinical care experienced by patients in complementary medicine (CM) consultations. Methods: A systematic review was undertaken of original research exploring patient perceptions of CM clinical care. Ten databases were searched: Alt HealthWatch, AMED, CINAHL Plus, MEDLINE Complete, Cochrane Library, PubMed, Proquest Medical Collection, PsycInfo, Social Sciences Citation Index and Psychology Collection. Studies were included which reported patient perceptions of consultation with CM practitioners and were excluded where experimental methods controlled the nature of consultation processes. Results: Findings of included studies (n = 34) were categorised under the a priori themes of empathy, empowerment and patient-centred care. This produced a substantial pool of qualitative data detailing patient-reported experiences which consistently confirmed occurrence of these themes in CM consultation. Quantitative data was correlative, yet was insufficient to definitively describe prevalence of such experiences. Conclusion: While it is evident that CM consultations provide a patient experience of empathy, empowerment and patient-centredness, further research is warranted to quantify this experience before it can be defined as characteristic of CM clinical care. Practice implications: This review draws attention to the potential role of CM as a resource for patients' psychosocial health needs.